Estudo da secagem de sementes de embaúba em leito fluidizado - Corrêa, Luciano Jacob (Universidade Federal de São Carlos, 2012)
Due to the importance of conservation of ecosystems and having Cecropia glaziovi.S as a pioneer species of the Tropical Forests, this plant becomes indispensable in reforestation areas altered wild. The drying operation is fundamental in the improvement of seeds, since it is not a seed recalcitrant. There is currently interest in studies of convective drying of the seeds on bed furniture, as in previous search has been shown to occur in fixed bed preferential channels and agglomerations of particles. The objective of this work is to study the fluidized bed capable of carrying out the drying of seed of native plants with the maintenance of physical and physiological properties. The comparison between the methods of decomposition and scraping the inflorescences wet and dry extraction showed that the wet method is more suitable for this kind of seed. The fluid dynamics of the contact between the seed and the fluid was drawn from measurements of pressure drop and air flow rates increasing and decreasing the bed. Using the method of SOGAB, demonstrated the uniformity of velocity and temperature in the entrance region of the measuring cell. The analyze the fluid allowed to obtain the information on the fluidisation characteristics curves, while the drying tests enabled the knowledge of the effects of temperature and velocity of the drying air on the properties of the seeds. The data obtained were compared with empirical equations and the resulting semi-empirical literature. Since the Page equation is analyzed between the equations that best represents the experimental data according to statistical criteria adopted. Assessment of germination, regardless of substrates, which are germitest paper germibox tanks and soil showed that the seeds are suitable for replanting. It was possible to obtain, after drying, seed with adequate humidity values for the storage and physiological qualities contribute to the perpetuation of these embryos and dissemination of higher plants in nature.
Keywords: Engenharia química; Leito fluidizado; Secagem; Sementes; ENGENHARIAS::ENGENHARIA QUIMICA